The use of wearable data in health insurance and ethical challenges in Indonesia - Nadia Hafrisa; Sudarningayuti Lintang Wahyu Azahra; Cahya Arbitera; Riswandy Wasir (PT WIM Solusi Prima, 2026)
Advances in digital technology in the healthcare sector are driving increased use of wearable data across various services, including health insurance. Data generated by wearable devices such as physical activity, heart rate, and sleep patterns offer opportunities to support more dynamic health risk assessments, the development of more personalized premiums, and the strengthening of preventive approaches within the health insurance system. This trend indicates a shift in the insurance system from a reactive approach toward a data-driven and preventive approach. This study employs a literature review approach by examining relevant scientific articles from databases such as Google Scholar, PubMed, and Garuda. The analysis focuses on literature regarding the utilization of wearable data in health insurance as well as the accompanying ethical considerations. The findings indicate that wearable data holds significant potential in supporting the transformation of a data-driven health insurance system; however, its implementation still faces limitations regarding privacy, data security, and the readiness of regulations specifically governing the use of digital health data. Additionally, the use of wearable data raises ethical challenges, such as the potential for misuse of health data and the possibility of unequal treatment of insurance participants based on their health conditions.In Indonesia, regulations regarding the protection of digital health data are still evolving and do not yet fully address the technical aspects of using wearable data in health insurance systems. Therefore, there is a need to strengthen regulations and policies grounded in digital ethics to ensure that the use of wearable data is safe, fair, and responsible.